COMPARISON OF AGGREGATE GRADINGS FOR HIGHWAYS BASED ON THEIR VOIDS CHARACTERISTICS. - Sharma Raj Pal; Rao S.Koteswara (My University, 2025)
The packing and void characteristics of blends of various aggregate size groups were studied. It was observed that the void structure developed in an aggregate blend depends on the size-ratios and volumetric proportions of their components. The void structure was distinguished as 'composite' or 'filler' type depending on the size-ratios of the components. An experimental investigation program was carried out for comparison of three standard specified gradings with skip gradings possessing the same voids-ratios as the standard grading, but with their components proportioned at or near the balanced stage. The Marshall characteristics of such skip-graded paving mixtures are observed to be superior to those of the standard continuous-graded mixtures. This appears to show that the strength characteristics of a paving mixture are influenced by the voids-structure as well as the voids-volume.